Factors associated with level of birth preparedness among pregnant mothers at Kerugoya county referral hospital - Karimi, Olive W.; Murigi, Mary W.; Pertet, Anne; Odawa, Careena O. (International Journal Of Community Medicine And Public Health, 2017)
Background: Birth preparedness is the advance preparation made by an expectant mother which ensures access to skilled care. In Africa, the risk of pregnancy related deaths is 300 times more than in the developed world. In Kenya, out of 10 expectant mothers who access antenatal care services only 4 deliver in a health facility. Methods: This was a descriptive cross sectional study conducted at outpatient Maternal Child Health and Family Planning Clinic at Kerugoya County Hospital. The study utilized convenience sampling technique to determine the study population. The research instruments were an In-depth interview guide and semi-structured questionnaires. Data was managed using SPSS and analysis done using descriptive statistics and Chi-square tests. Statistical significance was set at p<0.05. Results: A sample of 202 women participated in the study. 47.5% of the participants were adequately prepared for birth. Having a higher level of education was significantly associated with birth preparedness (p=0.021). The number of children per woman had a significant influence on level of birth preparedness with women who had no children less likely to be prepared for birth compared to those with one or more children (p=0.002). Clients who attended Antenatal Care (ANC) at least 3 times were prepared for birth compared to those who visited either once or twice (p=0.027). Conclusions: Overall, women of reproductive age lack birth preparedness. There is therefore need to enhance birth preparedness awareness campaigns at ANC visits targeting women in their third trimester.